2020
DOI: 10.1111/jns.12404
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term walking ability and patient satisfaction after lower limb functional surgery in patients affected by Charcot‐Marie‐Tooth disease: A retrospective study

Abstract: Structural foot deformities consequent to Charcot Marie Tooth (CMT) can be treated by functional surgery (FS). This study aims to evaluate both long‐term walking ability and patients' satisfaction in CMT subjects who underwent FS during their lifetime. We conducted a retrospective observational study. Age, sex, CMT type, comprehensive surgical history, current walking ability assessed by the Walking Handicap Scale (WHS) and patients' global impression of change (pGIC) were retrieved from a custom database mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The majority of patients were male (18/25, 72%) and had CMT1A due to chromosome 17 duplication (17/25, 68%). The mean CMTES v2 was 11 (SD 4.5) (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of patients were male (18/25, 72%) and had CMT1A due to chromosome 17 duplication (17/25, 68%). The mean CMTES v2 was 11 (SD 4.5) (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Direct comparison with previous studies is difficult since all the studies so far performed have been retrospective and only few studies have looked at the long‐term outcome of foot and ankle surgery in CMT. Previous studies have used patients' satisfaction or self‐reported questionnaires such as the FFI, but not validated physical outcomes 6‐9 . Only one prospective study has been recently performed and this was on a cohort of 21 children undergoing a combination of surgical procedures 5 using validated physical, functional, parent‐self reported and biomechanical outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations